2005
DOI: 10.1088/0953-2048/18/12/020
|View full text |Cite
|
Sign up to set email alerts
|

Tensile fracture behaviour of RE-123 coated conductors induced by discontinuous yielding in Hastelloy C-276 substrate

Abstract: We investigated the intrinsic strain effect on critical current, Ic, and tensile fracture behaviour in the RE-123 coated conductors (RE =  Y, Dy or Sm) with Hastelloy C-276 substrates. It is found that the SmBCO coated conductors exhibit an intrinsic strain effect on Ic which is similar to that in the DyBCO ones. Ic decreases monotonically with increasing applied tensile strain but it can recover reversibly up to the strain of 0.32% when the strain is relieved. Quenching occurred for the coated conductors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 18 publications
8
50
1
Order By: Relevance
“…For YBCO CC tapes without stabilizers, it was reported that annealed Hastelloy showed discontinuous yielding [13]. However, the I c degradation shown for the stabilized YBCO CC tape tested in this study, represented that the surround copper stabilizer may have contributed in the homogeneous I c degradation even with such behaviour of the Hastelloy substrate.…”
Section: Resultscontrasting
confidence: 49%
See 2 more Smart Citations
“…For YBCO CC tapes without stabilizers, it was reported that annealed Hastelloy showed discontinuous yielding [13]. However, the I c degradation shown for the stabilized YBCO CC tape tested in this study, represented that the surround copper stabilizer may have contributed in the homogeneous I c degradation even with such behaviour of the Hastelloy substrate.…”
Section: Resultscontrasting
confidence: 49%
“…If the critical tolerance stress/strains of I c in CC tapes depend on the mechanical properties such as the yield stress/strain or proportional stress/strain limit, then characterization would be easy. But there are cases when the irreversible strain limit could be located prior to yielding of the substrate material, especially in the case of Ag-coated CC tapes [12][13]18]. What makes the characterization complicated is due to the multi-layered structure of the CC tapes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that this significant irreversible degradation of I c in CC tapes is attributed to the cracking of the superconducting film due to its innate brittleness. Hence, for engineering purposes we need to measure the maximum strain that can be applied before the superconductor breaks [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…According to the engineering requirements to such a system, the surge and steady values of a fault current should not exceed a maximum permissible value. The high temperature superconducting tapes of the second generation (2G HTS) which have been shown to withstand high stress and strain without degradation [1,2] are seem to be the most suitable material for this application. Therefore, detailed studies of the electric and thermal characteristics of these tapes with multiple current overloads are needed.…”
Section: Introductionmentioning
confidence: 99%